2015
DOI: 10.1039/c5py00780a
|View full text |Cite
|
Sign up to set email alerts
|

Controlled release of anticancer drug Paclitaxel using nano-structured amphiphilic star-hyperbranched block copolymers

Abstract: In the present study, two amphiphilic star-hyperbranched copolymers, poly(methyl methacrylate)-b-poly(2-hydroxyethyl methacrylate) (PMMA-b-PHEMA), with different hydrophilic PHEMA segment content (PMMA-b-PHEMA-1, and PMMA-b-PHEMA-2) were synthesized and their drug loading and release profiles were examined by using paclitaxel (PTX) as a model drug. Drug loading capacity and encapsulation efficiency were found to be similar in both polymers. Encapsulation efficiency found to be prominent with 98% and 98.5% for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
9

Relationship

8
1

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 38 publications
(66 reference statements)
0
43
0
Order By: Relevance
“…This way, amphiphilic star‐hyperbranched poly(methyl methacrylate)‐ block ‐poly(2‐hydroxyethyl methacrylate) (PMMA ‐b ‐PHEMA) possessing hydrophobic hyperbranched core and hydrophilic chains were obtained, which were used for drug delivery systems ( Scheme ) …”
Section: Light‐induced Self‐condensing Polymerizationmentioning
confidence: 99%
“…This way, amphiphilic star‐hyperbranched poly(methyl methacrylate)‐ block ‐poly(2‐hydroxyethyl methacrylate) (PMMA ‐b ‐PHEMA) possessing hydrophobic hyperbranched core and hydrophilic chains were obtained, which were used for drug delivery systems ( Scheme ) …”
Section: Light‐induced Self‐condensing Polymerizationmentioning
confidence: 99%
“…The method is based on the reactivity difference of the photochemically generated radicals toward double and triple bonds . In another work, we have shown that hyperbranched poly(methyl methacrylate) (PMMA)‐ co ‐poly(2‐bromoethyl methacrylate) copolymers can be prepared by using Mn 2 (CO) 10 photochemistry which were further shown to be suitable materials for drug delivery systems …”
Section: Introductionmentioning
confidence: 99%
“…In the literature, among the poly(methyl methacrylate)‐ b ‐poly(2‐hydroxyethyl methacrylate) (PMMA‐ b ‐PHEMA) copolymers‐based DDS, star‐shaped systems were synthesized by radical polymerization and tested for the release of anticancer drugs. Geyik et al used amphiphilic star‐hyperbranched copolymers based on PMMA‐ b ‐PHEMA to release paclitaxel, a chemotherapeutic agent . Seleci et al evaluated a nanostructured amphiphilic star‐hyperbranched PMMA‐ b ‐PHEMA block copolymer as DDS of the anticancer drug doxorobucin .…”
Section: Introductionmentioning
confidence: 99%